ANALISIS MONDAY EFFECT DAN FRIDAY EFFECT PADA INDEKS LIKUIDITAS 45 DI BURSA EFEK INDONESIA - Fitri Wulandari; Nur Diana (Universitas Islam Malang, 2018)
ABSTRACTMany researchers find Monday effect and Friday effect phenomenon thatare against the efficient market concept which determine that daily stock returnswill be stable. The purpose of this research are to (1) determine the difference ofreturn that occurs on Monday through Friday, (2) to find out the Monday effecton stock trading, (3) to determine the Friday effect on stock trading, and (4) toknow the influence of partial and simultaneous the trading day on the daily stockreturns in Indonesia Stock Exchange. The method used in this research is eventstudy. And the data used in this research is secondary data, while the sample usedis LQ 45 daily stock returns listed in the Stock Exchanges period on August 2016until July 2017 was taking 36 companies by using purposive sampling. Thisresearch was using analysis technique of one sample t-test. The result showedthat: (1) There were significant differentiation between daily stock returns ontrading days in a week in Indonesia Stock Exchange. (2) There weredifferentiation caused by Monday effect on LQ 45 companies in Indonesian StockExchange (IDX). (3) There were differentiation caused by Friday effect on LQ 45companies in Indonesian Stock Exchange (IDX).Keywords: Return, Monday effect, Friday effect